2006
DOI: 10.1007/s10350-006-0574-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Indications for Colectomy in Ulcerative Colitis Patients are Different According to Patient's Clinical Background

Abstract: In ulcerative colitis patients, the risk factors and indications for colectomy were different according to the patient's clinical background. Our findings may help to predict patients with ulcerative colitis who have a high risk for colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…While this is in agreement with one large scale multivariate analysis,17 multiple studies have suggested pancolitis to be a strong predictor of colectomy 10,11,18,19. It also has been clearly demonstrated that patients with pancolitis have a higher rate of dysplasia and colorectal cancer 20.…”
Section: Discussionsupporting
confidence: 88%
“…While this is in agreement with one large scale multivariate analysis,17 multiple studies have suggested pancolitis to be a strong predictor of colectomy 10,11,18,19. It also has been clearly demonstrated that patients with pancolitis have a higher rate of dysplasia and colorectal cancer 20.…”
Section: Discussionsupporting
confidence: 88%
“…Although the observed prevalence fits within the previously reported range, it was quite low compared to that observed in Western countries [10,17,21] and is closer to the results of studies initiated in Asian countries [20,22]. Differences in clinical patterns of UC between races or ethnic groups may help us to understand the etiology or pathogenesis of the disease.…”
Section: Discussionsupporting
confidence: 81%
“…The exact mechanism by which hormonal fluctuations affect the degree of inflammation and symptoms in IBD has yet to be fully identified, but investigation at the cellular level has demonstrated an effect of estrogen in the control of pathogenic inflammation [35]. In contrast, according to a report in Japan [17], one of the predictors of colectomy was the male gender, which suggests that male patients are likely to be more resistant to medical treatment or have more aggressive clinical manifestations. Regardless, the effects of gender or sex hormones on disease course and prognosis are still unclear, and further investigations are needed to clarify these points.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Total proctocolectomy is the procedure of choice for patients with MUC especially in the elective setting. A three-stage operation might be necessary if the risk for postoperative anastomotic leak is high [24]. Thus, not surprisingly, the second most common surgery in the series was restorative proctocolectomy with ileal pouch-anal anastomosis.…”
Section: Discussionmentioning
confidence: 96%